MicroRNA and Long Non-coding RNA Regulation in Skeletal Muscle From Growth to Old Age Shows Striking Dysregulation of the Callipyge Locus - Mikovic, Jasmine; Sadler, Kate; Butchart, Lauren; Voisin, Sarah; Gerlinger-Romero, Frederico; Della Gatta, Paul; Grounds, Miranda D.; Lamon, Séverine (Frontiers in Genetics, 2018)
MicroRNAs (miRNAs) undergo high levels of regulation in skeletal muscle development and control skeletal muscle mass, function and metabolism over the lifespan. More recently, the role of long non-coding RNAs (lncRNAs) in skeletal muscle regulation has started to emerge. Following up on our recent study describing the expression pattern and putative roles of 768 miRNAs in the quadriceps muscle of mice at early life stages, we used a high-throughput miRNA qPCR-based array to assess the expression of the same miRNAs in 28-month old male mouse quadriceps muscle. In addition, we report the expression patterns of lncRNAs playing a putative role in muscle development and adaptation from growth to old age. Twelve miRNAs were significantly downregulated in 28-month old muscle when compared with 12-week old muscle. Ten of them clustered at the Dlk1-Dio3 locus, known as ‘Callipyge’, which is associated with muscle development and hypertrophy. This collective downregulation was paralleled by decreases in the expression levels of the maternally expressed imprinted LncRNA coding genes Meg3 and Rian stemming from the same chromosomal region. In contrast, the paternally expressed imprinted Dlk1-Dio3 locus members Rtl1, Dio3 and Dlk1 and the muscle related lncRNAs lncMyoD1, Neat_v1, Neat_v2 and Malat1 underwent significant changes during growth, but their expression levels were not altered past the age of 12 weeks, suggesting roles limited to hyperplasia and early hypertrophy. In conclusion, collective muscle miRNAs expression gradually decreases over the lifespan and a cluster of miRNAs and maternally expressed lncRNAs stemming from the Callipyge locus is significantly dysegulated in ageing muscle. The Dlk1-Dio3 locus therefore represents a potential new mechanism for age-related muscle decline.